2017
DOI: 10.1002/advs.201700645
|View full text |Cite
|
Sign up to set email alerts
|

Modified Back Contact Interface of CZTSe Thin Film Solar Cells: Elimination of Double Layer Distribution in Absorber Layer

Abstract: Double layer distribution exists in Cu2SnZnSe4 (CZTSe) thin films prepared by selenizing the metallic precursors, which will degrade the back contact of Mo substrate to absorber layer and thus suppressing the performance of solar cell. In this work, the double‐layer distribution of CZTSe film is eliminated entirely and the formation of MoSe2 interfacial layer is inhibited successfully. CZTSe film is prepared by selenizing the precursor deposited by electrodeposition method under Se and SnSex mixed atmosphere. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 21 publications
(5 reference statements)
0
54
0
Order By: Relevance
“…The lattice expansion is mainly caused by Cd doping, due to the larger ionic radius of Cd 2+ (0.92 Å) than of Zn 2+ (0.74 Å) or Cu + (0.74 Å). [43][44][45] In addition, extensive stacking faults and dislocations are present in the IFFT pattern of CdS for the RT device, while these are not observed on the corresponding HT device. This indicates that the new phase Cu 2 S formed after annealing eliminates the dislocations of the RT device, which is more favorable for reducing the carrier recombination.…”
Section: Energy and Environmental Science Papermentioning
confidence: 98%
“…The lattice expansion is mainly caused by Cd doping, due to the larger ionic radius of Cd 2+ (0.92 Å) than of Zn 2+ (0.74 Å) or Cu + (0.74 Å). [43][44][45] In addition, extensive stacking faults and dislocations are present in the IFFT pattern of CdS for the RT device, while these are not observed on the corresponding HT device. This indicates that the new phase Cu 2 S formed after annealing eliminates the dislocations of the RT device, which is more favorable for reducing the carrier recombination.…”
Section: Energy and Environmental Science Papermentioning
confidence: 98%
“…Kesterite Cu 2 ZnSn(S,Se) 4 (CZTSSe) as a kind of promising candidate for photovoltaic material is booming for scalable photovoltaic applications due to its low‐cost, earth‐abundant elemental constituents, and suitable bandgap . However, kesterite‐based solar cells with a 12.6% record efficiency is still much younger and far lower than the well‐developed chalcopyrite photovoltaics based on Cu(In,Ga)Se 2 (CIGS) having already demonstrated a power conversion efficiency (PCE) of over 20% .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a thick MoS 2 layer at the CZTS/Mo interface can influence the total series resistance of the device [41]. However, Zhang et al recently demonstrated 7.2% efficient CZTS solar cells without having any MoS 2 layer [57]. By the way, HR-TEM suggest around 50 nm of MoS 2 has been formed in our solar cells (Fig.…”
Section: Complete Czts Solar Cell Characterizationmentioning
confidence: 68%